Developing the Students’ Ability in Understanding Mathematics and Self-confidence with VBA for Excel - Martin Bernard; Eka Senjayawati (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2019)
Visual Basic Application for Excel is a simple program language and has the power to process data quickly. The utilization of math functions in Microsoft Excel can help work on Excel display more interactive so that teachers can create props inside Excel. The advantages of Microsoft Excel than other mathematical software are the many math functions and images available in the form of shapes or pictures. The availability of VBA, math and image functions in Microsoft Excel help teachers to design the creation of media related to mathematics learning, especially to develop the ability of junior high school students who have difficulty to connect mathematics lessons with basic mathematics knowledge requirements. By using VBA for Excel, the ability of junior high school students to improve in the usual way significantly with a t-test with 0.006 0.05.  Furthermore, there is an association between the students’ self-confidence and their mathematical comprehension skills with a contingency coefficient of 0.525 including a moderate association.